Efecto de la fertilización orgánica sobre las variables agronómicas y su calidad de forraje en la Morus alba - Lara Andrade, Steven Alberto (2022)
Fertilization in species such as mulberry can be considered as the most influential factor in biomass production; the absence of a good fertilization program would result in a low nutritional quality of the forage harvested. Therefore, the present study was carried out with the objective of evaluating the use of different levels of compost in the production of M. alba in order to determine the ideal dose of application, for which it was necessary to select a lot for the implantation of the crop in the Campus "La Maria" of the State Technical University of Quevedo. A Completely Randomized Design (CRD) was used with four treatments and four replications, the treatments used were T0, T1, T2 and T3 and the doses supplied for each treatment were 0, 100, 200 and 300 kg of compost/ha respectively, while for the comparison of means the Tukey test was used (p≤ 0.05). The variables evaluated were: plant height (m), leaf weight (g plant-1), stem weight (g plant-1), leaf/stem ratio, growth rate (g/day), biomass (g plant-1), production (T ha-1), dry matter (DM), organic matter (OM), crude protein (CP), neutral detergent fiber (NDF) and acid detergent fiber (FDA). The results showed statistical equality between treatments (p>0.05) in each of the variables mentioned; however, the treatment with the highest CP was T2 (200 kg of compost/ha) with 23.19%.